Simultaneous Health Risk Behaviors in Adolescents Associated with Higher Economic Class in the Northeast of Brazil - Arley Santos Leão; Nara Michelle Moura Soares; Eliane Cristina de Andrade Gonçalves; Diego Augusto Santos Silva; Roberto Jerônimo dos Santos Silva; Sara Maria Thomazzi (The Scientific World Journal)
Design. The social, cultural, and economic context can be an important variable in the perception and adoption of risk behaviors in adolescents. Objective. The purpose of this study was to identify the prevalence of simultaneous health risk behaviors and associated socioeconomic factors in adolescents living in the metropolitan region of Aracaju, State of Sergipe, Brazil. Methods. The sample consisted of 2,207 high school students aged 13–18 years. The risk behaviors measured were “low levels of physical activity,” “excessive daily TV time,” “high consumption of alcoholic beverages on a single occasion,” “involvement in fights,” “smoking cigarettes,” “carrying firearms,” and “marijuana consumption.” Information was obtained through self-administered questionnaire. Results. Considering the results, it was observed that female adolescents and those aged up to 16 years were less likely to have two or more health risk behaviors compared to males and those aged 17 years or more, respectively. It was also found that both high- and middle-income level adolescents had higher prevalence of having two or more health risk behaviors. Conclusions. It was concluded that male adolescents older than 16 years with better socioeconomic level were more exposed to the simultaneous presence of several health risk behaviors.